Kandungan Bahan Aktif Fomesafen dalam Biji Kedelai dan Kacang Hijau dari Tanaman yang Ditumbuhkan pada Tanah Bekas Paparan Reflex - Murni Dwiati; Iman Budisantoso (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
A research has been conducted to understand the responses of soybean and mungbean to the persistence of Reflex residuals in soils referring to its active substance contents, i.e. fomesafen, in the plants grown in Reflex-exposed soils. The study was carried out experimentally in glass house from June to November 2003 employing Completely Randomized Design (CRD) with treatments arranged factorial. Two factors were used, the first of which was plant species (soybean and mungbean) while the second was Reflex concentrations (0, 25, 50, 100, and 200 ppm). Each treatment combination was replicated three times. The parameters examined comprised of fomesafen contents in the seeds, number of seeds per pod, weight of 100 seeds, and weight of total seeds. To measure fomesafen contents in the seeds, Gas Liquid Chromatograph with ECD detector and column containing 10% OV-101 chromosorb WHF 80/100 mesh of 2m lengths and 3 mm diameter was applied. Fomesafen residuals in the soils of 5 month persistence had no harmful effect on both soybean and mungbean plants. As well, they had no significant effect on the production variables of both plants. Soybean seeds planted in the 5-month Reflex-exposed soils still contained fomesafen while the corresponding mungbean seeds did not.